Derivation of the Duchenne muscular dystrophy patient-derived induced pluripotent stem cell line lacking DMD exons 49 and 50 (CCMi001DMD-A-3, ∆49, ∆50) - Gabriella Spaltro; Vera Vigorelli; Federica Casalnuovo; Pietro Spinelli; Elisa Castiglioni; Davide Rovina; Stefania Paganini; Marina Di Segni; Patrizia Nigro; Cristina Gervasini; Giulio Pompilio; Aoife Gowran (Stem Cell Research, 2017)
Duchenne muscular dystrophy (DMD) is caused by abnormalities in the dystrophin gene and is clinically characterised by childhood muscle degeneration and cardiomyopathy. We produced an induced pluripotent stem cell line from a DMD patient's dermal fibroblasts by electroporation with episomal vectors containing: hL-MYC, hLIN28, hSOX2, hKLF4, hOCT3/4. The resultant DMD iPSC line (CCMi001DMD-A-3) displayed iPSC morphology, expressed pluripotency markers, possessed trilineage differentiation potential and was karyotypically normal. MLPA analyses performed on DNA extracted from CCMi001DMD-A-3 showed a deletion of exons 49 and 50 (CCMi001DMD-A-3, ∆49, ∆50).